Consumer Research on CeleBreak Barcelona - Mohammed Taher Hamdan S (2021)
Performing consumer research is a continuous process that never ends; it provides insight on various aspects of the consumer which can help the business adapt and grow to the consumer demands. With the increasing rhythm of life people are less able to participate in recreational team sports which increased demand on the phenomenon of pick-up sports. CeleBreak is a company with a new concept where they organize pick-up football through an app to make pick-up football more convenient to the average person. This research aims to analyse the consumers of CeleBreak pick-up football app. By connecting the aspects of the experience economy and understanding different consumer experience theories combined with methods of market segmentation and data analysis the research is able to develop a better understanding to the point of view of the CeleBreak user. The study combines both qualitative and quantitative data, statistical analysis of CeleBreak user and game data combined with direct observation performed on CeleBreak users. The study segmented CeleBreak users from demographical, geographical, and behavioural point of view. It also evaluates the growth of new users' and sorts out the effectiveness of different marketing methods used to acquire new users. It also sheds light on customer satisfaction of the CeleBreak app and how it has decreased with time. Furthermore, it splits user satisfaction into 3 parts and explains the features of each part from the users’ point of view. In addition to that, it recognizes other CeleBreak franchises and analyses their growth and accomplishments. Direct observation performed for a period of 3 months that provided reliable insight on users in different stages of using the CeleBreak app. The research will provide a whole sum of understanding on aspects such as user behaviour in different stages of app usage, different user segments, user satisfaction, user growth and how its effected and user growth that is connected to the overall growth of CeleBreak. Combining statistical analysis with direct observation helped the research provide reliable and statistically proved insight of CeleBreak users.